Using the Lifeworld Approach to Improve HIV Testing. Issue 6 (18th August 2019) - Wurm, Michael; Neumann, Anja; Wasem, Jürgen; Biermann-Stallwitz, Janine
ABSTRACT: Major guidelines for HIV recommend that testing should be provided in a way that is adapted to the lifeworld of groups at risk. However, precise definitions as to what adaption to the lifeworld means are missing. Therefore, this research project evaluated how the lifeworld approach can be operationalized in regard to HIV testing and how voluntary counseling and testing services can use this approach to improve efficacy. A survey for VCT providers in Germany showed a limited number of factors influencing the adaption to the lifeworld of groups at risk. The opening hours, the number of languages used in public relations, and the comfort of the waiting zone are important for all clients. For men who have sex with men, information material for use in social networks and peer volunteers are relevant. Intravenous drug users are concerned with participation, (low) costs, and counseling. For migrants, continuing staff training and anonymity are important.